3D‐QSAR studies and molecular design on a novel series of pyrimidine benzimidazoles as Lck inhibitors. Issue 9 (26th February 2014) - Xie, Wen Guo; Fang, Dan Qing; Wu, Wen Juan; Zhang, Rong; Zeng, Guo Hua; Ma, Shao Jie; Wu, Jing Heng; Shen, Yong
<x xml:space="preserve">Abstract</x> The development of selective lymphocyte‐specific kinase (Lck) inhibitors has attracted much attention for the research of the treatment of T‐cell mediated autoimmune and inflammatory diseases. In the present work, three‐dimensional quantitative structure–activity relationship (3D‐QSAR) analyses are performed on a novel series of 4‐amino‐6‐benzimidazole‐pyrimidines acting as Lck inhibitors. The established 3D‐QSAR models show significant statistical quality and satisfactory predictive ability, with high q2 and R2 values: the comparative molecular field analysis (CoMFA) model (q2 = 0.802, R2 = 0.991), and the comparative molecular similarity indexes analysis (CoMSIA) model (q2 = 0.731, R2 = 0.982). The systemic external validation indicates that both CoMFA and CoMSIA models are quite robust and possess high predictive abilities with <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0fkdgf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Rpred2</alternatives> values of 0.881 and 0.877, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0fkdh0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />rm2</alternatives> values of 0.897 and 0.847, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0fkfbr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />rm(LOO)2</alternatives> values of 0.897 and 0.850, and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0fkf96" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />rm(overall)2</alternatives> values of 0.897 and 0.854, respectively. Several key structural features accounting for the inhibitory activities of these compounds are discussed. Based on established models and design considerations, six new compounds with significantly improved activities are theoretically designed, which still await experimental confirmation and evaluation. These theoretical results may provide a useful reference for understanding the action mechanism and designing novel potential Lck inhibitors. © 2014 Wiley Periodicals, Inc.